Angiofibroma, a rare cardiac tumour in children - Gayen, G; Pan, A; Dasbakshi, K; Mukherjee, P (Journal of College of Medical Sciences-Nepal, 2013)
Angiofibromas, located in any other sites than nasopharynx are unusual. Cardiac angiofibromas are a very rare cardiac tumours in comparison to rhabdomyomas which are the commonest in the children. We report a right ventricular tumour in a10 year old girl which was excised under cardiopulmonary bypass successfully and diagnosed as angiofibroma on histopathology. Journal of College of Medical Sciences-Nepal, 2012, Vol-8, No-4, 51-54 DOI: http://dx.doi.org/10.3126/jcmsn.v8i4.8702